2014
DOI: 10.1007/s12664-014-0495-6
|View full text |Cite
|
Sign up to set email alerts
|

Positioning high-dose radiation in multidisciplinary management of unresectable cholangiocarcinomas: Review of current evidence

Abstract: Cholangiocarcinoma is a rare malignancy of the bile ducts. The current standard of care for unresectable nonmetastatic disease is doublet systemic chemotherapy, which provides a median survival of 11.7 months. Although chemoradiation is a therapeutic option that provides almost equivalent or superior survival, the lack of level I evidence presents a major hurdle in routinely recommending it within multidisciplinary clinics. This mini review presents the current evidence on the use of chemoradiation for unresec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…Unfortunately, the results recorded in recent years (22–27) did not show a significant improvement of patients' outcome, which remain similar to those recorded in previous decades (69). An improvement in the clinical results could derive from innovative combinations with systemic therapies and/or from a more intensive use of most advanced RT techniques (IMRT, VMAT, IGRT).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Unfortunately, the results recorded in recent years (22–27) did not show a significant improvement of patients' outcome, which remain similar to those recorded in previous decades (69). An improvement in the clinical results could derive from innovative combinations with systemic therapies and/or from a more intensive use of most advanced RT techniques (IMRT, VMAT, IGRT).…”
Section: Discussionsupporting
confidence: 79%
“…Locally advanced unresectable disease is the most common presentation of BTC. Some studies demonstrated that combined-modality therapy based on chemoradiation +/-BT boost could reduce pain and improve LC, biliary decompression, and OS (69). In a recent retrospective study on 37 patients with unresectable extrahepatic CC treated with chemoradiation, 1-year LC and OS rates were 90 and 59%, respectively (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Radical radiation with or without chemotherapy and or brachytherapy is associated with equivalent survival. 3 Local failure continues to dominate patterns of failure in patients with resectable and unresectable cholangiocarcinoma treated with surgical or nonsurgical treatments. [4][5][6][7] The impact of radiation response in EHCC is best demonstrated in a cohort of patients undergoing neo-adjuvant chemo-radiation prior to liver transplantation wherein 42% patients had complete pathological response in the resected livers.…”
Section: Introductionmentioning
confidence: 99%